Kutch in 1957 - Planning Commission (Planning Commission, 1957)
'Kutch in 1957' is a captivating caption, for those who have lived in this land and dreamt for its progress. Only a few years back, with its precarious and uneven rainfall, its meagre communications and isolation from the rest of India, this land was a source of constant anxiety. I know, many able sons of this soil were feeling disheartened and disillusioned, not because there was no progressive change but even the possibilities of such a change were getting few and remote. The people from Kutch were migrating out of this place and settling themselves in other parts of India and even outside India. Today, an equal number of people have settled outside Kutch.
Development Department of the Kutch Secretariat